HASIL MENGGAMBAR RAGAM HIAS PADA BAHAN KAYU MELALUI MODEL LEARNING CYCLE DI SMPN 1 KARANGPLOSO - Sutisnowati Sutisnowati (Center of Language and Cultural Studies, 2016)
This study describes implementation of learning cycle model to improve attaintment of drawing decorations using wood material. Classroom action research design with two circles was used. The study took place in SMPN 1 Karangploso Malang in March to April 2015 involving 30 students of 7th grade. Data of this study were processes of instruction to draw decorations. This study revealed (1) average score in circle I are: scetching 69, implementing 68.96, and drawing 71.87’; and in circle II: 80.8 scetching, 82.4 implementing and 82.3 drawing; (2) In circle II process of raising question, answering teacher’s questions, learning efforst, participation and self-independence, respectively are: very good (1.3%), good (52.2%, fair (44.2%), and low (2,2%); in circle II were: very good (21.8%), good (68.8%), fair (3.1%), and low (0%). Learning cycle models in this study improves learning process and attainment on drawing on material woods.